Do credit default swaps affect the time-varying cointegration between PIIGS's sovereign interest rates?. (24th August 2019) - Fonseca, José Soares Da
This paper shows that the linkages between the sovereign interest rate spreads of Greece, Ireland, Italy, Portugal and Spain, during the period from the beginning of 2008 till the end of 2014, were significantly dependent on credit default swaps (CDSs). Three rolling autoregressive distributed lag (ARDL) models were used to estimate the interest rates cointegration: one restricted model that includes only interest rates as variables, one restricted model that includes CDSs and the unrestricted model that joins CDSs to interest rates in the estimations. The frequency of cointegration phases is higher both in the restricted model with credit default swaps and in the unrestricted model than in the restricted model with interest rates. However, the non-cointegration phases were predominant in all the models. The output of rolling ARDL estimations was included in logit models which give the probability that a cointegration phase in one domestic market occurs simultaneously with an identical phase in the other markets.